VD_FINDINFO PC 13/08 - 7/2011 vom 19. März 2011 - VD Tribunal cantonal (2011)
OBLIGATION DE RENSEIGNER, RESTITUTIONEN GÉNÉRAL, PRINCIPE DE LA BONNE FOI | 25 al. 1 LPGA, 25 al. 2 LPGA, 24 OPC-AVS/AI, 4 al. 1 OPGA